2000
DOI: 10.1067/mtc.2000.109538
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diltiazem prophylaxis on the incidence and clinical outcome of atrial arrhythmias after thoracic surgery

Abstract: After major thoracic operations, prophylactic diltiazem reduced the incidence of clinically significant atrial arrhythmias in patients considered at high risk for this complication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 38 publications
(71 reference statements)
0
64
4
1
Order By: Relevance
“…Calciumchannel blockers such as verapamil and diltiazem have been shown to have no effect in reducing arrhythmias after noncardiac surgery and our study suggests the same (14% versus 11.5%, p = 0.76) [22,23]. An interesting hypothesis that statins or NSAIDs might decrease inflammation and hence contribute to decreased atrial fibrillation has been propagated but our study did not find a similar association [24].…”
Section: Discussioncontrasting
confidence: 57%
“…Calciumchannel blockers such as verapamil and diltiazem have been shown to have no effect in reducing arrhythmias after noncardiac surgery and our study suggests the same (14% versus 11.5%, p = 0.76) [22,23]. An interesting hypothesis that statins or NSAIDs might decrease inflammation and hence contribute to decreased atrial fibrillation has been propagated but our study did not find a similar association [24].…”
Section: Discussioncontrasting
confidence: 57%
“…In our study, we found no statistically signifi cant diff erence between patient groups with and without diltiazem prophylaxis, suggesting that in our patients, POAF occurred as a complication of lung resection comparably often with and without diltiazem prophylaxis. So, we could not confi rm the report by Amar et al on diltiazem therapy and its signifi cant POAF rate reduction 3 . Our speculation that patients with diltiazem prophylaxis generally have somewhat slower ventricular response during POAF (median 150; without any prophylaxis, median 160), which could have some protective properties per se, was not confi rmed by statistical analysis.…”
Section: Discussioncontrasting
confidence: 49%
“…Lobectomies and pneumonectomies are recognized as high risk procedures with POAF incidence above 15% 1 . Among drugs recommended for the prophylaxis of POAF and equivalent postoperative arrhythmias is diltiazem, a calcium antagonist 2,3 . It has few side eff ects and, with respect to known contraindications, it is well tolerated, especially in patients with chronic obstructive pulmonary disease (COPD) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Arrhythmia was also one of the main causes of death in patients with lung cancer during postoperative period, and it directly affected the postoperative recovery (21,22). It could be seen that the occurrence of arrhythmia after lung cancer surgery was influenced by a variety of factors, such as preoperative ECG abnormalities, advanced ages, and hypertension, operation modes.…”
Section: Discussionmentioning
confidence: 99%